Wide scan imaging with swept-source optical coherent tomography for glaucoma diagnosis - Hong, Eun Hee; Shin, Yong Un; Kang, Min Ho; Cho, Heeyoon; Seong, Mincheol (PloS one, 2018)
To determine glaucoma-discriminating abilities of macular and circumpapillary retinal nerve fiber layer (cpRNFL) thickness measurements of wide scan (12X9mm) using swept-source optical coherence tomography (SS-OCT) compared to measurements of standard macula and disc scans (6 X 6 mm). This retrospective chart review study included 60 glaucomatous and 62 healthy eyes of total 122 subjects who visited a glaucoma clinic and were examined with wide, standard macula, and standard disc scans of SS-OCT (DRI-OCT-1 Atlantis; Topcon Inc., Tokyo, Japan) on the same day. Thickness measurements of the ganglion cell layer plus inner plexiform layer (mGCIPL), mGCIPL plus nerve fiber layer (mGCC), and total retinal layer (TRL) were assessed in wide and standard macula scans. Thickness measurements of cpRNFL were assessed in wide and standard disc scans. The repeatability and agreement of measurements taken in each scan were evaluated using intraclass correlation coefficients (ICCs). The abilities of parameters to discriminate between glaucoma and normal groups were assessed using areas under receiver operating characteristic curves (AUCs). The repeatability and agreement of all parameters showed high ICC values (all ≥ 0.800). AUCs for mGCIPL thickness were 0.710-0.847 and 0.701-0.836 in standard macula and wide scans, respectively. AUCs for cpRNFL thickness were 0.749-0.902 and 0.726-0.897 in standard disc and wide scans, respectively. There were no significant differences in AUCs between wide and standard scans. The agreement between SS-OCT wide and standard scans for mGCIPL, mGCC and cpRNFL measurements were excellent. As the glaucoma-discriminating ability of wide scans was comparable to that of standard macula/disc scans, a single wide scan can replace separate standard macula/disc scans for evaluating glaucoma.